Evaluation of depression training program for community pharmacists in Indonesia: A quasi-experimental study - Nisa Febrinasari, Anna Wahyuni Widayanti, Yayi Suryo Prabandari, Satibi Satibi (Journal of Applied Pharmaceutical Science, 2025)
The main treatment for depression is medication, and pharmacists play a crucial role in the medication therapy management. However, inadequate training for community pharmacists (CPs) becomes the main barrier to effective treatment. This study aims to evaluate the effectiveness of the depression training program (DTP) in improving depression literacy, self-efficacy, and communication skills as well as reducing stigma among CPs in Indonesia. A quasi-experimental study with a pretest–posttest control group design was conducted, involving 120 CPs in Yogyakarta. The CPs’ depression literacy, self-efficacy, and stigma in both intervention and control groups were compared. The ANCOVA test was used to analyze the data. The results showed that the DTP with a pretest as the covariate reduced the CPs’ internalized stigma (p = 0.000), increased their self-efficacy (p = 0.000), and improved the depression literacy (p = 0.000) compared with those of the control group. However, their communication skills required further improvement even after the training. This program effectively enhanced the CPs’ competencies in literacy and self-efficacy and reduced the stigma to providing pharmaceutical care for patients with depression. It can be appropriate for continuing education programs for pharmacists in Indonesia or another country particularly those with small or nonexistent mental health budgets.
Keywords: Mental health, depression, community pharmacists, Indonesia